PROBLEMS OF LEARNING ISLAMIC RELIGIOUS EDUCATION AND ETHICS CASE STUDY AT SDN PATOKAN 1, KRAKSAAN PROBOLINGGO - Musrifa; Kurniawan Farid, Edi; Zaini, Bahruddin (Qawwam : The Leader's Writing, 2025)
The aim of this research is to examine the problems of learning Characteristics and Islamic Religious Education (PAI) at SDN Patokan 1 Kraksaan, Probolinggo Regency. Character education and PAI have an important role in developing the morals and character of students from the start of life. However, in practice, there are usually a number of problems that hinder the efficient achievement of learning objectives. This research uses a qualitative approach with a case study method. Data collection was carried out through observation, interviews with PAI teachers, school administrators and students, as well as documentation of educational activities.The research results obtained show that there are learning problems of Islamic religious education at SMA Negeri 13 Gowa include: 1. Students who It's easy to get bored in learning because of the motivation of the teacher lacking, 2. Educators who are less varied in using methods, 3. Very minimal facilities and infrastructure are also one of the causes of learning problems.